Conversão biológica de sulfato a sulfeto a partir de resíduos de gesso sonicados. - Araujo, Gleice Paula de (2023)
The sulfate ion is one of the main anions found in waters contaminated by industrial waste, especially those resulting from improper disposal in the gypsum industry. This research aimed to discover the optimal conditions for effective biological sulfate reduction. This was achieved through sonication of gypsum residues to make sulfate ions more accessible to bacteria in a consortium collected from gypsum mine sludge in the Araripe Gypsum Polo, Pernambuco, using sewage as a nutrient source. Experiments were conducted in Erlenmeyer flasks equipped with agitation and temperature control, operating at ambient pressure to create ideal conditions for the growth of Sulfate-Reducing Bacteria (SRBs) present. The culture medium, based on Starkey's medium (DONG et al., 2020), was modified by reducing sodium lactate content and incorporating sewage. The gypsum, after undergoing pretreatment with ultrasonic waves (US) at 30 kHz for 12 minutes, was aimed at activating and making sulfate ions available, resulting in greater exposure to SRBs more effectively. A fractional factorial design was used to determine the critical factors for biological sulfate reduction. Independent variables included temperature, pH, initial sulfate concentration, and COD/[SO4=] ratio, with the percentage reduction of sulfate as the response variable. A 24 experimental design, specifically a Central Composite Rotatable Design (CCRD), was employed to identify the optimal conditions for biological sulfate reduction in gypsum residues. The optimized conditions were 32°C temperature, pH 7.5, initial sulfate concentration of 2200 mg/L, and COD/[SO4=] ratio of 4, resulting in a 93.15% reduction percentage using the desirability function. The pretreatment of gypsum residues with ultrasound aimed to activate and make sulfate ions available, enhancing their exposure to SRBs. The combination of sonication of gypsum residues and the use of sewage not only improved bioreduction efficiency but also reduced process costs on a larger scale due to the high cost of lactate as a carbon source.